Work related musculoskeletal disorders (WMSDs) : a reference book for prevention (London, 1997)
"Work-related musculoskeletal disorders, or WMSDs, are a significant problem throughout the world. It was previously thought that WMSDs would decline in tandem with the decline in repetitive work. This has not been the case; indeed some authorities believe WMSDs will be one of the major occupational disease of the early twenty-first century. This book aims to help prevent WMSDs. Its core themes are identification, evaluation, action, and change. It is the result of a unique collabration between leading international experts. The group examines the work-relatedness of WMSDs, and explores and synthesizes information and techniques which seek to prevent WMSDs. In a truly collective effort, the authors in their various chapters link work with tendon, nerve, muscle, joint, vascular, and non-specific or multiple tissue disorders; explore individual susceptibility; assess occupational risk factors; describe health and hazard surveillance techniques; discuss the management of change; outline training and education programmes; and overview medical management. "